Community-Based and Digital Marketing Strategies in Early Childhood Islamic Education: A Case Study at RA Muslimat NU 016 Mayak Ponorogo - Ma'rufah, Afni (Global Education Journal, 2025)
This study explores how RA Muslimat NU 016 Mayak Ponorogo implements strategic educational marketing to increase new student enrolment amid growing competition, particularly in religious-based early childhood education. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The study examines the planning, implementation, and evaluation of marketing strategies, involving school principals, teachers, staff, and parents. Findings reveal that a combination of community-based outreach and digital promotion—especially through word-of-mouth and social media—has led to a 16% increase in student enrolment over the past two years. These strategies also helped enhance the institution’s public image and parental trust. The study provides practical recommendations for educational institutions seeking to improve enrolment through adaptive, low-cost, and community-integrated marketing approaches.